El enfermo mental en el medio penitenciario español - Domínguez, Anabel Cerezo (International e-journal of criminal sciences, 2016)
This paper aims to address the current situation of the mentally ill in prisons from two different points of view. First, it pays special consideration to the compliance with a safety measure in a penitentiary psychiatric hospital applicable to individuals declared not criminally responsible under the concurrence of an alleged anomaly or psychic alteration provided for in art. 20.1 of the Criminal Code. Second, it highlights the problems involved in the application of vicarial system to those individuals declared almost incompetent (art. 21.1). An exploratory research in a Spanish prison shows the situation of the mentally ill that fulfill their sentences in ordinary prisons.